Conciliation: matrimonial disputes - Ali Mohamed, Ashgar Ali; Tan, Yeak Hui (CLJ Publication, 2020)
It must be emphasised that in matrimonial disputes what matters between the parties is not who is right but what is right for their harmonious relationship to continue. Therefore, an alternative mode of dispute resolution such as conciliation is most befitting to deal with matrimonial disputes. Conciliation can assist the disputing parties to re-establish trust and respect, and help to prevent damage to an ongoing relationship. Having said the above, the conciliation of matrimonial disputes is discussed with reference to the Law Reform (Marriage and Divorce) Act 1976 (‘LR (MD) Act’)